Unani Perspectives on Dyslipidemia: An Integrative Review of Classical Concepts and Contemporary Relevance - Rasool, Ishrat; Ali, Sadique; Khizar , Niyazi Abdullah (Journal of Drug Delivery and Therapeutics, 2025)
Background: This review examines dyslipidemia from both Unani and contemporary perspectives. Dyslipidemia is one of the most prevalent pathological conditions in modern times, primarily resulting from unhealthy dietary habits and sedentary lifestyles. Due to its high atherogenic potential, it is a major contributor to systemic disorders, particularly cardiovascular diseases and cerebrovascular accidents. In Unani medicine, dyslipidemia is attributed to the predominance of Baroodat (coldness) in the liver and the body, which disrupts the phlegmatic balance, impairs fat metabolism, and leads to abnormal accumulation. Accordingly, therapeutic interventions that temper hepatic and systemic coldness and restore metabolic harmony may offer significant benefitsMethods: Literature for this study was obtained from electronic databases, including PubMed, Web of Science, ScienceDirect, EMBASE, Google Scholar, ResearchGate, and Elsevier, as well as from major resource libraries containing Unani books and manuscripts relevant to the topic.Results: Lipids and phlegm share significant similarities in origin, nature, pathophysiology, and complications. Despite differences in terminology, both systems converge common outcomes such as vascular obstruction, metabolic inefficiency, and heightened cardiovascular risk. This suggests that classical descriptions of Balghamī disorders may represent early interpretations of lipid dysregulation.Conclusion: Combining biomedical and Unani perspectives provides a more integrated view of dyslipidemia. Such an approach can enhance early recognition, guide context-specific interventions, and contribute to better cardiovascular risk management.Keywords: Dyslipidaemia, lipids, Phlegm, Phlegmatic disorders, Unani Medicine